My best friend's wedding [videorecording (DVD)] - Roberts, Julia, 1967-; Mulroney, Dermot; Diaz, Cameron; Everett, Rupert; Bosco, Philip; Walsh, M. Emmet, 1935- (Columbia TriStar Home Entertainment, 2001)
Friends from college make a pact to marry each other if they are not married by 28. When Michael gets engaged Julianne will stop at nothing to stop the wedding.